Ego-depletion and motor skill performance under pressure—experimental effects of a short term virtual-reality based mindfulness breathing meditation with integrated biofeedback - Matthias Wagner; Alissa Wieczorek (Scientific Reports, 2024)
Abstract Ego-depletion describes a state of mind, where the capacity for self-control is temporarily depleted after a primary self-control action. The aim of this study was to investigate whether a brief virtual reality-based mindfulness breathing meditation with integrated biofeedback can be considered an effective strategy to counteract the detrimental effects of ego depletion on motor skill performance under pressure. The study included two experiments, each of them designed as counterbalanced cross-over trials and based on an a priori sample-size calculation. Within each experiment, participants completed two appointments in a randomly assigned order, during which they were asked to perform 20 basketball free throws (N = 18; Experiment 1) or 20 penalty kicks at a football goal in four target squares (N = 16; Experiment 2) under pressure pre and post the following conditions: Stroop-test-induced ego depletion followed by a 15 min resting break, Stroop-test-induced ego depletion followed by a 15 min virtual reality-based mindfulness breathing meditation with integrated biofeedback. Results indicate that, in comparison to a resting break, a brief virtual reality-based mindfulness meditation with integrated biofeedback can counteract the detrimental effects of ego-depletion (Experiment 2) and enhance motor skill performance under pressure (Experiment 1, 2) Implications for researchers and practitioners are derived in light of the identified methodological limitations.